PERANCANGAN SISTEM INFORMASI MONITORING PRODUKSI SEPATU BERBASIS WEB PADA PT. BKM - Joko Suwarno (Institut Sains dan Teknologi Nasional, 2022)
ABSTRACT BKM is a Fans brand shoes manufacturer from Indonesia which has many customers and started its business as a sports shoes trader. In the processing of data in the company found problems about recording the quantity of goods on the information board and minimize human error in the recording process. Therefore a system was made that could make it easier to monitor production at PT. BKM. This system is made using PHP programming language in data storage using MySQL database. In making this monitoring system required several methods such as data collection, observation, and interviews. After that the relationship diagram (ERD) design, interface design, and proposed implementation are carried out. The author hopes that the design of the system can get to the application stage. So that this production monitoring system can be used in PT. BKM. From observations at PT. BKM can be concluded by using a production monitoring system that can help managers in monitoring the product quantity and can make it easier to make reports in making decisions. Keyword : Monitoring, PHP, MySQL